The "Sūtra on Transforming the Female Form": Unpacking an Early Medieval Chinese Buddhist Text - Balkwill, Stephanie (Journal of Chinese religions, 2016)
In this article I seek to show that T564, the Sūtra on Transforming the Female Form (Zhuan nüshen jing 轉女身經), is not only a composite text which integrates narrative and doctrinal material from a number of other sūtras, but also that it was likely written in early medieval China. The identification of this text as a Chinese indigenous creation is important for the text has enjoyed a long and rich transmission history across East Asia, and also because it contains a new argument for why a woman needs to become a man in order to become a Buddha. By analyzing and presenting the text in such a way, I wish to reveal the important place that composite, indigenous, and other "spurious" texts have held in the development of radically new doctrines within the Mahāyāna and thus argue for their further inclusion in modern studies of the tradition.